Clicks or Bricks? Online Shopping Adoption in Australia - Clemes, Michael D.; Bicknell, Kathryn; Li, Xuedong; Long, Nicole (Business and Economic Research, 2021)
<p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Purpose: This research identifies and ranks the decision factors associated with online shopping adoption in Australia. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Design/Methodology/Approach: Primary data for this study was collected with self-administered questionnaires and analysed using EFA and logit regression. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Findings: The following factors, ranked in order of importance, influence online shopping behaviour in Australia: perceived risk, service quality, website factors, brand image, product variety and Australian product loyalty. The findings also show that demographic characteristics also influence the probability that Australian consumers will shop online. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Originality/value: This is the first empirical study in which the decision factors influencing Australian consumers’ decisions to shop online are examined. The research contributes to the empirical literature on online shopping from a theoretical perspective as the modelling framework can be used to analyse online shopping behaviour in different cultural settings. Longitudinal studies based on the modelling framework can also be undertaken to identify emerging decision factors and to track the changes in importance of the current factors. The results will also enable retailers to make informed decisions on their existing or future shopping channels.